The last 6 Gyr of dark matter assembly in massive galaxies from the Kilo Degree Survey. Issue 1 (16th September 2017) - Tortora, C.; Napolitano, N. R.; Roy, N.; Radovich, M.; Getman, F.; Koopmans, L. V. E.; Verdoes Kleijn, G. A.; Kuijken, K. H.
Abstract: We study the dark matter (DM) assembly in the central regions of massive early-type galaxies up to z ∼ 0.65. We use a sample of ∼3800 massive (log M ⋆ /M⊙ > 11.2) galaxies with photometry and structural parameters from 156 deg 2 of the Kilo Degree Survey (KiDS), and spectroscopic redshifts and velocity dispersions from Sloan Digital Sky Survey (SDSS). We obtain central total-to-stellar mass ratios, M dyn / M ⋆, and DM fractions, by determining dynamical masses, M dyn, from Jeans modelling of SDSS aperture velocity dispersions and stellar masses, M ⋆, from KiDS galaxy colours. We first show how the central DM fraction correlates with structural parameters, mass and density proxies, and demonstrate that most of the local correlations are still observed up to z ∼ 0.65; at fixed M ⋆, local galaxies have larger DM fraction, on average, than their counterparts at larger redshift. We also interpret these trends with a non-universal initial mass function (IMF), finding a strong evolution with redshift, which contrast independent observations and is at odds with the effect of galaxy mergers. For a fixed IMF, the galaxy assembly can be explained, realistically, by mass and size accretion, which can be physically achieved by a series of minor mergers. We reproduce both the R e – M ⋆ and M dyn / M ⋆ – M ⋆ evolution with stellar and dark mass changing at a different rate. This result suggests that the main progenitor galaxy is merging with less massive systems, characterized by a smaller M dyn / M ⋆, consistently with results from halo abundance matching.